Exploring Metamaterials’ Structures Through the Relaxed Micromorphic Model: Switching an Acoustic Screen Into an Acoustic Absorber - Rizzi, Gianluca; Collet, Manuel; Demore, Félix; Eidel, Bernhard; Neff, Patrizio; Madeo, Angela (Frontiers in Materials, 2021)
While the design of always new metamaterials with exotic static and dynamic properties is attracting deep attention in the last decades, little effort is made to explore their interactions with other materials. This prevents the conception of (meta-)structures that can enhance metamaterials’ unusual behaviors and that can be employed in real engineering applications. In this paper, we give a first answer to this challenging problem by showing that the relaxed micromorphic model with zero static characteristic length can be usefully applied to describe the refractive properties of simple meta-structures for extended frequency ranges and for any direction of propagation of the incident wave. Thanks to the simplified model’s structure, we are able to efficiently explore different configurations and to show that a given meta-structure can drastically change its overall refractive behavior when varying the elastic properties of specific meta-structural elements. In some cases, changing the stiffness of a homogeneous material which is in contact with a metamaterial’s slab, reverses the structure’s refractive behavior by switching it from an acoustic screen (total reflection) into an acoustic absorber (total transmission). The present paper clearly indicates that, while the study and enhancement of the intrinsic metamaterials’ properties is certainly of great importance, it is even more challenging to enable the conception of meta-structures that can eventually boost the use of metamaterials in real-case applications.